في الجزائر ( SIGBUD،MSB ،SIGB) مشروع رقمنة المالية العم ومية: نحو أنظمة معلوماتية مدمجة لإدارة الميزانية والمحاسبة: Public finance digitization project: towards a common information system for budget management and accounting (SIGB, MSB, SIGBUD) in Algeria - لكحل محمد; لكحل حياة (Journal of North African Economies, 2025)
This study aims to highlight the gains from digitization, both for countries, individuals as well as in the preparation and execution of the general budget With regard to the case of Algeria, reference was made to the public finance digitization project in Algeria as a mechanism for updating public financial transactions through the unified information systems of the Ministry of Finance, which is represented in the integrated information system for the management of my budgets and the information system of the Directorate General of Accounting (MSB, SIGBUD, SIGB), which is part of the reform of my budgets for the year 2023, In addition to analyzing the performance of public finances in Algeria within the framework of the economic recovery plan (2020-2024) and its prospects within the framework of the new economic model 2030. The study concluded that Algeria is able to modernize public finances thanks to the information systems applied in the financial sector, and that it can then achieve financial sustainability. In return, it should strive to bridge the digital divide and improve the information and communication technology infrastructure.